A new criteria for acute on preexisting kidney dysfunction in critically ill patients - Dejiang Hong; Qinghuan Ren; Jie Zhang; Fubo Dong; Shiqiang Chen; Wei Dong; Xiaoyan Chen; Longwang Chen; Yongming Yao; Zhongqiu Lu; Guangju Zhao (Renal Failure)
Critically ill patients with preexisting kidney dysfunction (PKD) are at high risk for acute kidney injury (AKI). Nevertheless, there is no criteria for screening and classifying AKI in patients with PKD. In this study, after assessing relationship between the change in SCr from baseline and in-hospital mortality, a new criteria, named APKD, for identifying AKI in PKD was proposed. APKD defined AKI in critically ill patients with PKD as an absolute increase of ≥ 0.2 mg/dL in SCr within 48 h or an increase in SCr ≥ 1.1 times over baseline within 7 d. APKD detected more AKI among PKD patients compared with the other criteria. Additionally, the AKI patients identified by APKD but missed by the other criteria had higher mortality than those without AKI. APKD shows higher sensitivities than KDIGO criteria in predicating in-hospital mortality. APKD, but not the KDIGO, is effective for staging the severity of AKI in patients with PKD. In conclusion, APKD is more effective in screening and classifying AKI in critically ill patients with PKD compared with the earlier criteria, and it may helpful in guiding clinical treatment and predicting prognosis.